2010
DOI: 10.1029/2010jd014123
|View full text |Cite
|
Sign up to set email alerts
|

A critical remark on the applicability of E‐OBS European gridded temperature data set for validating control climate simulations

Abstract: [1] The study compares daily maximum (T max ) and minimum (T min ) temperatures in two data sets interpolated from irregularly spaced meteorological stations to a regular grid: the European gridded data set (E-OBS), produced from a relatively sparse network of stations available in the European Climate Assessment and Dataset (ECA&D) project, and a data set gridded onto the same grid from a high-density network of stations in the Czech Republic (GriSt). We show that large differences exist between the two gridd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 25 publications
1
63
0
Order By: Relevance
“…E-OBS has been widely used for regional climate model evaluation (e.g. Lorenz and Jacob 2010;Nikulin et al 2011;Samuelsson et al 2011;Torma et al 2011;Flaounas et al 2013;Stéfanon et al 2014) and has been comprehensively evaluated in the literature (Hofstra et al 2009(Hofstra et al , 2010Kysel and Plavcov 2010;Flaounas et al 2012;Herrera et al 2012). In the E-OBS version 10 used here substantial improvements were realized, especially by increasing the station density (around 2000 for v1 and v2 vs. more than 4200 stations for temperature and more than 7300 for precipitation in v10).…”
Section: Observations: E-obs Datasetmentioning
confidence: 99%
“…E-OBS has been widely used for regional climate model evaluation (e.g. Lorenz and Jacob 2010;Nikulin et al 2011;Samuelsson et al 2011;Torma et al 2011;Flaounas et al 2013;Stéfanon et al 2014) and has been comprehensively evaluated in the literature (Hofstra et al 2009(Hofstra et al , 2010Kysel and Plavcov 2010;Flaounas et al 2012;Herrera et al 2012). In the E-OBS version 10 used here substantial improvements were realized, especially by increasing the station density (around 2000 for v1 and v2 vs. more than 4200 stations for temperature and more than 7300 for precipitation in v10).…”
Section: Observations: E-obs Datasetmentioning
confidence: 99%
“…Unfortunately, a number of studies have shown a potential weakness of this dataset in regions of sparse data (see, e.g. Kyselý and Plavcová, 2010;Herrera et al, 2012;Maraun et al, 2012, for the Czech Republic, Spain and UK, respectively). Hofstra et al (2009) compare MAP and EOBS (first version) over the GAR domain, finding a general underestimation of EOBS, larger errors in the Alps, and an overestimation of extreme precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the RKK method showed a similar performance to the E-OBS data set (Haylock et al 2008), and was similarly limited in regions with low station density. Kyselý and Plavcová (2010) recently demonstrated this for the E-OBS data set by comparison with an alternative data set that was generated from a high-density network in the Czech Republic.…”
Section: Resultsmentioning
confidence: 99%